The Effect of Problem Based Learning (PBL) Model on Students' Critical Thinking Ability in Sound Wave Material - Cahyani, Tia Rahmi; Dwikoranto; Prahani, Binar Kurnia; Admoko, Setyo (Indonesia Approach Education, 2023)
Education is a process of fostering and developing human resources that are directly beneficial for educating the nation's life. This study aims to describe the critical thinking ability of students in class XI of Senior High School with the application of problem-based learning (PBL) physics learning model. The results of the research are in the form of learning implementation, critical thinking ability, and students' responses. The type of research used is Quasi exsperimental design with Non-equivalent control group design. The research instruments consisted of test observation sheets, critical thinking ability test sheets, and response questionnaire instrument sheets. The results showed the results of the implementation of physics learning with a problem-based learning (PBL) learning model on critical thinking ability, which was implemented with a score of 91.11% and 92.85% in the first meeting and second meeting respectively in the very good category. The problem-based learning (PBL) learning model has a significant effect on the critical thinking ability of students on sound wave material by 81.27%. Students' responses after applying the physics learning of the Problem Based Learning (PBL) model to critical thinking ability get an average percentage of 85.90% in the very good category.